Synthesis and Characterization of Copper Complex of Salicylaldehyde Benzoyl Hydrazone - Shrestha, Sabita; Maharjan, Sudha (Journal of Nepal Chemical Society, 2013)
Copper complex of type [Cu(SBH)2] was synthesized and characterized by different analytical procedure and spectral studies. The complex was insoluble in common organic solvents and it has melting point in between 254-258°C. Infrared spectrum showed the bonding through enolic oxygen and azomethine nitrogen. The electronic spectral studies showed that the Cu(II) is in tetrahedral coordination environment. DOI: http://dx.doi.org/10.3126/jncs.v29i0.9231 Journal of Nepal Chemical Society Vol. 29, 2012 Page: 11-17 Uploaded date : 12/3/2013